Optimising Malaysia’s power mix for a sustainable future: a multi-scenario modelling approach - Wing Thye Woo; Yuen Yoong Leong; Wai Sern Low; Jin Soong Liew; Chean Chung Lee (Fulbright Review of Economics and Policy)
Purpose – This study employs advanced modelling to assess the effectiveness of Malaysia’s current energy policies in achieving a low-carbon future. By optimising a 100% renewable energy mix, including energy storage, the research identifies pathways to decarbonise the power sector while minimising costs. These findings will inform the development of future policies. Design/methodology/approach – This study employs the Stockholm Environment Institute-developed Low Emissions Analysis Platform (LEAP) and Next Energy Modeling system for Optimization (NEMO) to construct and optimise a comprehensive Malaysian power sector model. The model encompasses both electricity supply, including diverse electricity generation sources and demand across key sectors. Three scenarios – existing policy, optimised existing policy and more ambitious policy (near-zero emissions) – are analysed. Findings – Solar photovoltaic (PV) is the dominant technology, but realising its full potential requires significant grid upgrades. While natural gas expansion underpins Malaysia’s decarbonisation strategy, solar and storage offer a cleaner and potentially cost-effective alternative. Rapid technological advancements in clean energy increase stranded asset risk for new gas power plants. Malaysia’s abundant bioenergy resources need more tapping. This can contribute to decarbonisation and rural development. Transitioning to a fully renewable grid necessitates substantial investments in energy storage and grid infrastructure. While falling battery costs and regional interconnection can mitigate costs, careful consideration of potential disruptions and cost fluctuations is essential for resilience. Research limitations/implications – Energy sector modelling results are inherently dependent on input assumptions, such as future technology costs, resource availability and fossil fuel prices. These factors can be highly uncertain. While this study did not conduct sensitivity analyses to explore how variations in these assumptions might affect the results (e.g. cost variations across scenarios, technology mix fluctuations), the core findings provide valuable insights into potential decarbonisation pathways for Malaysia’s power sector. Future studies could build upon this work by incorporating sensitivity analyses to provide a more comprehensive understanding of how key results might change under a wider range of future possibilities. Originality/value – This study co-optimises a 100% renewable energy mix for Malaysia, incorporating a comprehensive range of renewable resources, battery and pumped hydro storage. The research also provides a unique perspective on the interplay of philosophical underpinnings, psychological maturity and energy policy.